2019
DOI: 10.1111/apa.15006
|View full text |Cite
|
Sign up to set email alerts
|

Bone and joint complications and reduced mobility are associated with pain in children with cerebral palsy

Abstract: Aim To investigate the relationships between pain in the lower extremities and back, and spasticity, bone/joint complications and mobility. Methods Retrospective population‐based registry study. Participants (N = 3256) with cerebral palsy (CP), 2.5‐16 years of age, participating in the Swedish Cerebral Palsy Follow‐up Program were included. Spasticity was measured using scissoring and the Modified Ashworth Scale. Bone/joint complications consisted of hip displacement, range of motion, windswept posture and sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
2
12
3
Order By: Relevance
“…Pain was reported as only yes or no by the child or the parents, and there was no grading of the severity of the pain. This limitation may explain why the association between hip contracture and pain was not statistically significant in this study, contrary to the results by Schmidt et al 1 …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Pain was reported as only yes or no by the child or the parents, and there was no grading of the severity of the pain. This limitation may explain why the association between hip contracture and pain was not statistically significant in this study, contrary to the results by Schmidt et al 1 …”
Section: Discussioncontrasting
confidence: 99%
“…Cerebral palsy (CP) is one of the most common neurological disabilities in children, with a global incidence of 2–3 events per 1000 live births 1‐3 . Frequent symptoms of CP are impaired muscle function and increased muscle tone, which can decrease both the ability to stand and walk and contribute to the development of lower limb contractures 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social aspect of being able to keep up with their peers could also be one reason for the finding that few children were in FMS level 2-4 in our study. It has also been reported that pain in children with CP was primarily explained by bone and joint deformities, including knee flexion contracture, and additionally associated with reduced mobility, as evaluated with the FMS (Schmidt et al 2020). Another explanation could be economic factors: in Sweden, the assistive technology centers, at no cost to the family, provide assistive devices and aids such as wheelchairs.…”
Section: Knee Flexion Contracturementioning
confidence: 98%
“…Although the exact impact of knee flexion contracture and its contribution to the development of flexed knee gait is still not fully understood, it is associated with progressive deterioration of gait in the ambulating child (Bell et al 2002, Rodda et al 2006 and it results in difficulties maintaining functional standing, sitting, and transfer in non-ambulatory children (Miller 2005, Cloodt et al 2018). In addition, knee flexion contracture generates increased forces on the knee joint, which may cause pain (Rodda et al 2006, Steele et al 2012, Schmidt et al 2020.…”
mentioning
confidence: 99%